Implementation of Character Education: The Role of Teachers in Fostering a Hard-Working Attitude in Students - Sutikno Sutikno; Mudofir Mudofir; Andi Arif Rifa’i (STAI Hubbulwathan Duri, 2025)
This study investigates the role of teachers in fostering the character of hard work among students at SMP Nurul Islam Ngemplak. Emphasizing the importance of character education in schools, it explores how principals and teachers collaboratively support students' work ethic through instructional and environmental strategies. A qualitative case study approach was employed to gain in-depth insights. Data were collected through observations, in-depth interviews with school stakeholders, and document analysis. This triangulation ensured a comprehensive understanding of the practices used to develop students’ hard-working character. Findings indicate that teachers play a pivotal role in promoting a strong work ethic. They act as role models, incorporate the value of hard work into classroom activities, and cultivate a supportive learning environment. Additionally, the use of motivation and rewards strengthens students’ commitment to learning. These practices are consistent with existing character education theories, highlighting teachers as both facilitators and motivators. The study underscores the necessity of a school-wide commitment to character development. Successful reinforcement of a hard-working ethos relies on strategic integration of values into teaching methods and school culture. To enhance students' character, especially the value of hard work, schools should adopt comprehensive policies that include teacher training, curriculum adjustments, and structured reward systems. These efforts can cultivate a consistent and effective culture of diligence across the educational environment.